Spermidine attenuates chondrocyte inflammation and cellular pyroptosis through the AhR/NF-κB axis and the NLRP3/caspase-1/GSDMD pathway - Guo, Xiaocheng; Feng, Xinyuan; Yang, Yue; Zhang, He; Bai, Lunhao (Frontiers in Immunology, 2024)
Abstract Introduction Osteoarthritis (OA) is a prevalent chronic degenerative disease, marked by a complex interplay of mechanical stress, inflammation, and metabolic imbalances. Recent studies have highlighted the potential of spermidine (SPD), a naturally occurring polyamine known for its anti-inflammatory and antioxidant properties, as a promising therapeutic agent for OA. This study delves into the therapeutic efficacy and mechanistic pathways of SPD in mitigating OA symptoms. Methods Forty Sprague-Dawley rats were randomly assigned to four groups, including the CG (sham operation), model (anterior cruciate ligament transection [ACLT], and treatment (ACLT + two different doses of SPD) groups. In vivo, correlations between OA severity and different interventions were assessed by ELISA, X-rays, CT imaging, histological staining, and immunohistochemistry. In vitro, IL-1β was used to trigger chondrocyte inflammation, and SPD’s cytotoxicity was assessed in primary rat chondrocytes. Next, inflammatory markers, extracellular matrix (ECM) proteins, and pathway marker proteins were detected in chondrocytes administered IL-1β alone, SPD, or aryl hydrocarbon receptor (AhR) silencing, by qRT-PCR, Griess reaction, ELISA, Western blot, and immunofluorescence. Morphological alterations and pyroptosis in chondrocytes were examined by transmission electron microscopy (TEM) and flow cytometry. Results Our research reveals that SPD exerts significant anti-inflammatory and antipyroptotic effects on IL-1β-treated chondrocytes and in anterior cruciate ligament transection (ACLT) rat models of OA, primarily through interaction with the Aryl hydrocarbon receptor (AhR). Specifically, SPD's binding to AhR plays a crucial role in modulating the inflammatory response and cellular pyroptosis by inhibiting both the AhR/NF-κB and NLRP3/caspase-1/GSDMD signaling pathways. Furthermore, the knockdown of AhR was found to negate the beneficial effects of SPD, underscoring the centrality of the AhR pathway in SPD's action mechanism. Additionally, SPD was observed to promote the preservation of cartilage integrity and suppress ECM degradation, further supporting its potential as an effective intervention for OA. Discussion Collectively, our findings propose SPD as a novel therapeutic approach for OA treatment, targeting the AhR pathway to counteract the disease's progression and highlighting the need for further clinical evaluation to fully establish its therapeutic utility.